Comparison of Dynamic Versus Static Lag Screw Modes for Short Cephalomedullary Nails in the Treatment of Unstable Intertrochanteric Fractures: A Randomized Controlled Trial - Ruangsillapanan, MD, Naruepol; Rattanakitkoson, MD, Tana; Ittimongkonkul, MD, Teerayut (Journal of Southeast Asian Orthopaedics, 2022)
Purpose: To compare the static locked and sliding proximal lag screw modes of short cephalomedullary nail in the treatment of unstable intertrochanteric fractures. Methods: Ninety-four patients (age>60 years) with low energy unstable intertrochanteric fractures were randomized for treatment into two groups. They were treated with static and sliding proximal lag screw modes of short cephalomedullary nail. The pre-operative variables, operative time, fluoroscopy time, blood loss, tip apex distance, and reduction quality were recorded for each patient. Post-operative follow-ups were undertaken every other week until bone union or implant failure occurred. Plain anteroposterior and lateral radiographs (both hip) were obtained at all visits. Ipsilateral leg length discrepancy (LLD), radiographic union score for hip complications, and fixation failure were recorded. Results: The mean follow-up time was 16.7 months (range 12–24). The mean bone union times of static locked (n=35) and sliding proximal (n=34) screw mode groups were 12.4 weeks and more than 11.2 weeks, respectively; the difference was not significant (p=0.213). The ipsilateral LLD of the sliding proximal (mean 4 mm) and static locked (mean 2 mm) screw mode groups showed a statistically significant difference (p<0.001). Post-operative complications (lag screw perforated to hip joint, lag screw cutout from the femoral head, and excessive inferolateral lag screw sliding) developed in 8.82% patients in sliding proximal group, whereas, no complications were reported in the static locked group. Conclusions: Treatment of unstable intertrochanteric fracture using static locked proximal lag screw mode of cephalomedullary nail showed some advantages over sliding proximal lag screw in terms of less complication and ipsilateral LLD; however, the bone union times were not different. Therefore, a static locked proximal screw mode is preferable over sliding proximal screw mode in treating unstable intertrochanteric fractures.